Advances in the early diagnosis and therapy of inclusion body myositis. Issue 6 (November 2018) - Lilleker, James B.
Abstract : Purpose of review: To describe recent advancements in diagnostic and therapeutic approaches to inclusion body myositis (IBM). Recent findings: Our understanding of the implications of anti-cytosolic 5′-nucleotidase 1A autoantibody status in IBM and other diseases is increasing. Muscle imaging using magnetic resonance techniques and ultrasound is increasingly being performed and characteristic patterns of muscle involvement may help with diagnosis. Longitudinal imaging studies are likely to help with monitoring and as an outcome measure in clinical trials. Recent small-scale studies of Arimoclomol and Rapamycin have shown promising results and further investigation of these medications is ongoing. Exercise is likely to form an increasingly important facet of management of patients with IBM, but the optimal type of exercise programme to enrol patients in is not yet determined. Summary: Antibody testing and muscle imaging results may improve our ability to diagnose IBM and the availability of effective disease modifying treatments targeting novel non-inflammatory pathways could soon become a reality. It remains the duty of those involved in the management of patients with IBM to facilitate involvement in clinical trials and other research studies.